2015
DOI: 10.1089/thy.2014.0116
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Age and Disease Status as Predictors of Thyroid Cancer-Specific Mortality Using the Surveillance, Epidemiology, and End Results Database

Abstract: Background: Age at diagnosis is incorporated into all relevant staging systems for differentiated thyroid carcinoma (DTC). There is growing evidence that a specific age cutoff may not be ideal for accurate risk stratification. We sought to evaluate the interplay between age and oncologic variables in patients with DTC using the largest cohort to date. Methods: The Surveillance, Epidemiology, and End Results (SEER) database was queried to identify patients with DTC as their only malignancy for the period 1973 t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
75
2
4

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 113 publications
(83 citation statements)
references
References 26 publications
(22 reference statements)
2
75
2
4
Order By: Relevance
“…However, there is evidence that age adds to the risk of mortality starting at age 35 (14,15). Furthermore, recent studies by Orosco et al (16) and by Londero et al (17) have suggested that although age is an important prognostic factor, there is no specific age cut off which predicts survival. Recent studies by Yang et al (18) and Banerjee et al (19) using SEER data have also reported evidence that death increases progressively with increasing age and that age as a continuous variable may be more appropriate.…”
Section: Discussionmentioning
confidence: 99%
“…However, there is evidence that age adds to the risk of mortality starting at age 35 (14,15). Furthermore, recent studies by Orosco et al (16) and by Londero et al (17) have suggested that although age is an important prognostic factor, there is no specific age cut off which predicts survival. Recent studies by Yang et al (18) and Banerjee et al (19) using SEER data have also reported evidence that death increases progressively with increasing age and that age as a continuous variable may be more appropriate.…”
Section: Discussionmentioning
confidence: 99%
“…For mortality however, rates were increased in patients over 40 years old. In fact, most of the staging systems include age at the diagnosis as a significant prognostic factor (17). In several staging systems, such as TNM, AMES and MACIS, age has been adopted as a factor to be taken into account (18,19).…”
Section: Discussionmentioning
confidence: 99%
“…(20), it was also shown that the prognosis in patients with DTC has a bimodal curve where the risk of nodal recurrence is higher in patients younger than 20 and older than Although it has been recognized that mortality caused by thyroid cancer would be increased as from 35 years and with the advancing age (21), it has been recently observed that the AJCC staging could overestimate the protective effect of the lower age in patients with DTC, especially in the context of the metastatic disease, resulting in substaging of young patients (22). In fact, young patients with both T3 tumours or with N1b nodal disease have a worse prognosis than older adults within the same TNM stage (17). In addition (23), it has been shown that, in the case of papillary microcarcinoma, the ratio of patients with tumour progression, i.e., progression to clinical disease was lower in adults over 60 than in patients younger than 40 years of age.…”
Section: Discussionmentioning
confidence: 99%
“…The cancer-specific mortality rate is <5% of patients with PTC, and most patients have an excellent prognosis. [5] The removal of the residual thyroid tissue in the case of detected malignancy after lobectomy has practical benefits regarding patients' treatment. [6] Completion thyroidectomy (CT) is the conversion of the process to total thyroidectomy (TT) by the removal of the residual thyroid tissue after subtotal thyroidectomy.…”
mentioning
confidence: 99%
“…The reason for preferring lobectomy is to avoid unnecessary thyroidectomies in patients with fine needle aspiration (FNA) biopsy that is suspiciously malignant or those that are indeterminate following FNA. [5,6] Thyroid lobectomy is the recommended initial surgical approach in patients with solitary, cytologically indeterminate nodule, atypia of undetermined significance/follicular lesion of undetermined significance (AUS/FLUS), or follicular neoplasm/suspicious for follicular neoplasm (FN/ SFN) according to the 2015 American Thyroid Association (ATA) guidelines. However, this approach may be modified according to the clinical or sonographic characteristics of the patient and patient preference or molecular tests.…”
mentioning
confidence: 99%